Improving Health Clinic Performance through the Role of Entrepreneurial Leadership and Dynamic Capabilities - Nurcahyo, Chandra (BPJS Kesehatan, 2024)
This study aims to analyze the effect of entrepreneurial leadership on organizational performance by considering the mediating role of dynamic capability in the context of the digital era. This study employs a quantitative approach utilizing structural equation modeling (SEM) based on Partial Least Squares (PLS). A survey was used to gather data from 385 respondents from top management or owners of Small and Medium Enterprises (SMEs) Healthcare Clinics in Indonesia. Data was processed using SmartPLS software version 3.0. The results showed that entrepreneurial leadership has a positive and significant influence on dynamic capability (path coefficient = 0.777; t-statistic = 26.792; p = 0.000), entrepreneurial leadership has a positive and important impact on organizational performance (path coefficient = 0.306; t-statistic = 5.232; p = 0.000), dynamic capability has a positive and significant influence on organizational performance (path coefficient = 0.510; t-statistic = 8.994; p = 0.000),. In addition, dynamic capability acts as a mediator that strengthens the influence of entrepreneurial leadership on organizational performance, highlighting the importance of adaptation and innovation to face the challenges of the digital era. This study provides insights for clinical SME leaders to develop entrepreneurial leadership skills that can drive the organization's dynamic capabilities and improve performance amid the dynamics of the digital era. This study contributes to the literature on entrepreneurial leadership and dynamic capabilities by highlighting their relationship to organizational performance in the context of SME Clinics in digital transformation.